2018
DOI: 10.3892/ijo.2018.4253
|View full text |Cite
|
Sign up to set email alerts
|

RNF113A promotes the proliferation, migration and invasion, and is associated with a poor prognosis of esophageal squamous cell carcinoma

Abstract: Ring finger protein 113A (RNF113A) possesses a C3HC4 zinc finger domain and this domain is found in E3 ubiquitin ligase and is involved in tumorigenesis. To date, and at least to the best of our knowledge, there are no studies available which have investigated RNF113A in cancer. Thus, this study aimed to explore the role of RNF113A in the development of esophageal squamous cell carcinoma (ESCC). For this purpose, paraffin-embedded samples from 117 patients with ESCC were selected, as well as 41 pairs of fresh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…KIF15 may be a potential prognostic biomarker in bladder cancer [23]. RNF113A expression is correlated with a poor prognosis of esophageal squamous cell carcinoma [24]. GJB6 involves in glioma cell growth and proliferation, and DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…KIF15 may be a potential prognostic biomarker in bladder cancer [23]. RNF113A expression is correlated with a poor prognosis of esophageal squamous cell carcinoma [24]. GJB6 involves in glioma cell growth and proliferation, and DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“… 36 As an oncoprotein, RNF113A promoted cell proliferation, migration, and invasiveness in esophageal squamous cell carcinoma (ESCC). 37 In the study of genome-wide gene expression profiling of CRC and adjacent tissues by Sun and Qian, 38 UTP3 was identified as 1 of 20 hub genes in CRC. It suggested that UTP3 plays a vital role in the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, specimens were incubated overnight at 4°C with antibodies specific to Ki‐67 (1:100; Abcam) and MMP10 (1:100; Abcam) in an avidin‐biotin complex method. The signal was later amplified and visualized with a secondary antibody (Beyotime), followed by 3′‐diaminobenzidine chromogen 7,30,31 …”
Section: Methodsmentioning
confidence: 99%
“…After 24 h incubation, nonmigrated/invaded cells on the upper surface were removed with a cotton swab and cells migrated to the lower chamber were fixed with 4% methanol and stained with crystal violet. The number of migrated cells was recorded under a microscope (DM IL, Leica Microsystems) in five random fields and calculated as the average per field 2,7,31 …”
Section: Migration and Invasionmentioning
confidence: 99%
See 1 more Smart Citation